Reform of Bureau of Public Services in Framework of Prevention & Eradication of Corruption in Indonesia - Novita Ilmaris; Arpangi Arpangi (Universitas Islam Sultan Agung, 2021)
Corruption in Indonesia decreases public trust, especially in the case of public services where there are still many irregularities, such as a long time, convolution and a lot of costs, so that public service bureaucracy reform is needed to realize good governance. This study aims to identify and describe the reform of the public service bureaucracy in the context of preventing and eradicating corruption in Indonesia. This study uses a normative juridical approach, which is descriptive analytical. The data used is secondary data obtained through the research library, which is then analyzed qualitatively. The result of this research is that public service bureaucratic reform in the context of preventing and eradicating corruption in Indonesia is carried out by improving the quality of public services, which aims to create equal distribution of public service quality at all levels, both at the ministry / agency level to the regional level. Bureaucratic reform in public services emphasizes the importance of improving the quality of public services, with a focus on public interests, and upholding accountability and transparency.